USEFULNESS OF GASTRIC SUBMUCOSAL DISSECTION DEPTH TO EVALUATE SKILL ACQUIREMENT IN SHORT TERM TRAINING COURSES IN ESD: AN EXPERIMENTAL STUDY - YAMAZAKI,Kendi (2018)
ABSTRACT BACKGROUND: Endoscopic submucosal dissection (ESD) is a complex endoscopic procedure, with high rates of adverse events and technical difficulties. To overcome that problem, many training centers published the importance of animal models for skill acquirement in ESD. However, no study has used the submucosal dissection depth (DSUB) as a parameter to evaluate the learning curve in ESD, which might be a relevant factor since an optimal resection plane is important to achieve a curative resection and avoid intraoperative complications. OBJECTIVE: This study aimed to assess ESD skill acquirement after short-term training sessions by evaluating the submucosal dissection depth (DSUB) and the association with adverse events. METHODS: This experimental study included 25 experienced endoscopists in therapeuthic procedures (>5years) and 75 specimens resected by ESD (three resections / endoscopist). Learning parameters (resection time, size, en bloc resection rate, bleeding, perforation and submucosal dissection depth) were prospectively evaluated. The percentages of DSUB of all specimens resected were calculated. RESULTS: All specimens were resected from the gastric body (n=75). The mean size of the resected specimens was 23.97±7.2 mm. The number of adverse events, including bleeding, perforation, and death, were 17 (22.67%), 3 (4%), and 0 cases, respectively. The average mean time by the third dissection decreased from 28.44±9.73 to 18.72±8.81 min (P<0.001). The proportion of DSUB in the bleeding and non-bleeding group were respectively 37.97%±21.13% and 68.66%±23.99%, indicating a significant association between DSUB and bleeding incidence (P<0.001). The ROC curve analysis indicated a cut-off point of 61% (sensitivity, 64%; specificity, 94%) of submucosal dissection depth associated with bleeding. Therefore, when ESD was performed at a depth of >61% of the submucosal layer, the risk for bleeding during the procedure decreased (PPV, 0.97; 95% CI, 0.85-0.99). CONCLUSION: Improvement in the learning curve in ESD and a better cognitive ability were seen by the third dissection in these short term training courses. And a significant association between DSUB and the risk of bleeding.